A study of the effects of outdoor group building activities on the psychological well-being of 25-30 year old overtime employees in private enterprises in Shanghai, China - Ren, Danping (International Journal of Global Economics and Management, 2024)
Today, Shanghai is China's economic and trade center and one of China's mega cities, which leads to the fast pace of life in Shanghai. Some employees in private enterprises work overtime, which makes the happiness of employee’s plummet, and eventually leads to the increase of turnover rate, which leads to the loss of talents in the company. This paper focuses on the impact of overtime work on the psychological happiness of 25 to 30 year old employees in Shanghai private enterprises, and whether the intervention of outdoor team building activities can improve the happiness of employees. This paper will use the mixed research method of interview and questionnaire to explore the influence of 25-30 years old in Shanghai private enterprises on the psychological happiness of overtime workers. This study can improve the working happiness of people between 25 and 30 years old and improve work efficiency, help companies fill the talent gap and further development, provide relevant theoretical basis for applied psychology, and provide reference suggestions for human resources in Shanghai private enterprises to promote the enthusiasm of employees. (Disclaimer: Shanghai in this article refers to Shanghai, China)